Genetic developmental timing revealed by inter-species transplantations in fish - Fuhrmann, Jana; Buono, Lorena; Adelmann, Leonie; Martinez-Morales, Juan Ramón; Centanin, Lázaro (Development, 2020)
Skip to Next Section - The path from a fertilised egg to an embryo involves the coordinated formation of cell types, tissues and organs. Developmental modules comprise discrete units specified by self-sufficient genetic programs that can interact with each other during embryogenesis. Here, we have taken advantage of the different span of embryonic development between two distantly related teleosts, zebrafish (Danio rerio) and medaka (Oryzias latipes) (3 and 9 days, respectively), to explore modularity principles. We report that inter-species blastula transplantations result in the ectopic formation of a retina formed by donor cells - a module. We show that the time taken for the retina to develop follows a genetic program: an ectopic zebrafish retina in medaka develops with zebrafish dynamics. Heterologous transplantation results in a temporal decoupling between the donor retina and host organism, illustrated by two paradigms that require retina-host interactions: lens recruitment and retino-tectal projections. Our results uncover a new experimental system for addressing temporal decoupling along embryonic development, and highlight the presence of largely autonomous but interconnected developmental modules that orchestrate organogenesis.